Process and apparatus for CO2 capture and sequestration with immobilised carbonic anhydrase. (May 2014) - Li, L.; Hao, D.; Fu, M.
Abstract : As a globular zinc metallic enzyme of molecular mass 30, 000, carbonic anhydrase II (CA II, EC 4·2·1·1) is capable of catalysing the reversible hydration reaction of the molecules of CO2 at a maximum of 1·4×10 6 s −1, the process of which exhibits a crude intracellular enzyme extract containing CA II immobilised against an inert inorganic support and by exposing to high concentrations of CO2 gas while transferring CO2 to biocarbonate ions. The apparatus used consists of a packed tower type bioreactor flushed by countercurrent and a pump to compress into it the gas containing CO2 and a liquid solvent. The bioreactor holds CA being bound covalently to an inert inorganic support such as ceramsite. The CO2 of the gaseous phase gets diffused into the liquid phase, and the immobilised CA catalyzes the hydration of the CO2 that forms biocarbonate ions. The solution of ions is precipitated with the exogenously induced Ca 2+ to fix the biocarbonate ions. The apparatus to capture bio-CO2 is expected to efficiently remove CO2 from the exhausted gases of coal burning and fossil fuel combustion at a relatively low cost.